2017
DOI: 10.1093/europace/eux167
|View full text |Cite
|
Sign up to set email alerts
|

Bedside autonomic risk stratification after myocardial infarction by means of short-term deceleration capacity of heart rate

Abstract: Deceleration capacity assessed from short-term recordings is a strong and independent predictor of mortality and cardiovascular mortality after MI, which is complementary to existing risk stratification strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
3
11
0
2
Order By: Relevance
“…Most importantly, DC ref from 2-h ECG recordings had the best discrimination power of all calculated DCs. Similar with a recent study [40], our findings also indicate that short-term DC ref , especially from 2-h ECG recordings may be a more useful and better index for autonomic bedside risk stratification that as complementary to traditional HRV measures and clinical factors.…”
Section: Discussionsupporting
confidence: 90%
“…Most importantly, DC ref from 2-h ECG recordings had the best discrimination power of all calculated DCs. Similar with a recent study [40], our findings also indicate that short-term DC ref , especially from 2-h ECG recordings may be a more useful and better index for autonomic bedside risk stratification that as complementary to traditional HRV measures and clinical factors.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, DC cutoff value of 4.37 ms yielded sensitivity of 66.00% and specificity of 83.08% for predicting CAL, KD children with DC ≤ 4.37 ms (OR = 3.275) had an increased risk of CAL. In adults, it has been demonstrated that DC < 2.5 ms is significantly related to a higher risk of death after myocardial infarction, while DC > 4.5 ms is related to a lower risk 16,34 . Wei Hu's research found that DC was an independent risk factor for heart failure, with cutoff values of 4.55 ms in males and 4.85 ms in females 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Des Weiteren lassen sich periodische Komponenten auch aus stark verrauschten Signalen zuverlässig und sensitiv extrahieren. Die [10,12]). DC: Deceleration Capacity auf der PRSA-Methode basierte "Dezelerationskapazität des Herzens" (Deceleration Capacity -DC) quantifiziert spezifisch dezelerationsbezogene und damit vornehmlich vagal modulierte Oszillationen der Herzfrequenz (▶ Abb.…”
Section: Methoden Zur Ekg-basierten Risikoanalyseunclassified
“…In den ersten Studien wurde DC aus 24-Stunden-Aufzeichnungen gemessen. Eine neuere Studie konnte zeigen, dass sich DC auch aus 20-minütigen Kurzzeitmessungen berechnen lässt, was die praktische Anwendbarkeit im klinischen Alltag deutlich erleichtern kann [12].…”
Section: Methoden Zur Ekg-basierten Risikoanalyseunclassified